CFD Modeling of Hydrocarbon-Air System Hydrodynamics in Three Types of Column Reactors - H. Faraji; A.R. Habibi; E. Jalilnejad (Iranian Journal of Chemical Engineering)
In this study, hydrodynamic characteristics such as gas holdup (ε), liquid phase velocity, and mass transfer coefficient (kLa) for air-diesel system were modeled for bubble column (BCR), airlift (ALR), and airlift with the net draft tube (ALR-NDT) reactors at different superficial gas velocities ranging from 0.008 to 0.085 m s-1. A 3D two-fluid Eulerian-Eulerian model was developed using computational fluid dynamic (CFD) technique to model the three configurations of column reactors and predict the hydrodynamic parameters. The results of 3D-CFD modeling showed a good agreement with the experimental data where average error was less than 14 and 9% for ε and kLa, respectively. Although the vortex occurred in BCR and ALR at high gas velocities, however optimum liquid and gas circulation and distribution observed in ALR-NDT. Furthermore, the formation of dead zone (kLa = 0) in the reactors was studied, and the results revealed that ALR-NDT has a lower volume of dead zones (about 8%) in comparison with BCR and ALR. In order to reduce the dead zone in BCR and ALR systems, the location of gas diffuser and draft tube were investigated. The dead zone was decreased by 12% with shifting of gas diffuser to the bottom of the BCR. Also, by increasing the distance of gas diffuser from draft tube, the dead zone was decreased by 40% specifically near the walls of ALR. Meanwhile, the simultaneous shifting of gas diffuser and draft tube to lower position in ALR had no effect on dead zone formation and its distribution.